Functional Dystonia: Differentiation From Primary Dystonia and Multidisciplinary Treatments - Frucht, Lucy; Perez, David L.; Callahan, Janet; MacLean, Julie; Song, Phillip C.; Sharma, Nutan; Stephen, Christopher D. (Frontiers in Neurology, 2021)
Dystonia is a common movement disorder, involving sustained muscle contractions, often resulting in twisting and repetitive movements and abnormal postures. Dystonia may be primary, as the sole feature (isolated) or in combination with other movement disorders (combined dystonia), or as one feature of another neurological process (secondary dystonia). The current hypothesis is that dystonia is a disorder of distributed brain networks, including the basal ganglia, cerebellum, thalamus and the cortex resulting in abnormal neural motor programs. In comparison, functional dystonia (FD) may resemble other forms of dystonia (OD) but has a different pathophysiology, as a subtype of functional movement disorders (FMD). FD is the second most common FMD and amongst the most diagnostically challenging FMD subtypes. Therefore, distinguishing between FD and OD is important, as the management of these disorders is distinct. There are also different pathophysiological underpinnings in FD, with for example evidence of involvement of the right temporoparietal junction in functional movement disorders that is believed to serve as a general comparator of internal predictions/motor intentions with actual motor events resulting in disturbances in self-agency. In this article, we present a comprehensive review across the spectrum of FD, including oromandibular and vocal forms and discuss the history, clinical clues, evidence for adjunctive “laboratory-based” testing, pathophysiological research and prognosis data. We also provide the approach used at the Massachusetts General Hospital Dystonia Center towards the diagnosis, management and treatment of FD. A multidisciplinary approach, including neurology, psychiatry, physical, occupational therapy and speech therapy, and cognitive behavioral psychotherapy approaches are frequently required; pharmacological approaches, including possible targeted use of botulinum toxin injections and inpatient programs are considerations in some patients. Early diagnosis and treatment may help prevent unnecessary investigations and procedures, while facilitating the appropriate management of these highly complex patients, which may help to mitigate frequently poor clinical outcomes.